Methodological Foundations of Socio-Philosophical and Legal Analysis of Corruption - Manukyan, Yeranuhi; Stepanyan, Ani; Ilyushina, Marina (Տիգրան Մեծ)
Corruption remains a pervasive global issue with far reaching consequences for societies, economies, and the rule of law. To effectively understand and combat this com-plex phenomenon, a robust methodological foundation is essential for socio-philosophical and legal analysis. This article explores the key aspects of corruption analysis, highlighting the multidimensional nature of the problem. It emphasizes the need to examine systemic factors such as institutional weaknesses and transparency deficits, alongside understanding the individual and collective motivations that drive corrupt behavior. The article advocates for a multidisciplinary approach that integrates empirical research, theoretical frameworks, and ethical considerations to unravel the intricate dynamics of corruption. By delving into the economic, social, and political impacts of corruption, this analysis contributes to a comprehensive understanding of corruption‟s roots and consequences. The insights derived from this methodological exploration can inform the development of effective strategies to combat corruption and strengthen the foundations of a just and accountable society.
Keywords: Philosophy